Tuning the functionality of a carbon nanofiber-Pt-RuO2 system from charge storage to electrocatalysis - Balan, Beena K.; Kurungot, Sreekumar (Inorganic Chemistry, 2012)
Chemical-functionalization-induced switching in the property of a hybrid system composed of a hollow carbon nanofiber (CNF) and Pt and RuO2 nanoparticles from charge storage to electrocatalysis is presented. The results of this study show how important it is to have a clear understanding of the nature of surface functionalities in the processes involving dispersion of more than one component on various substrates including carbon nanomorphologies. When pristine CNF is used to decorate Pt and RuO2 nanoparticles, random dispersion occurs on the CNF surface (C-PtRuO2). This results in mainly phase-separated nanoparticles rich in RuO2 characteristics. In contrast to this, upon moving from the pristine CNF to those activated by a simple H2O2 treatment to create oxygen-containing surface functional groups, a material rich in Pt features on the surface is obtained (F-PtRuO2). This is achieved because of the preferential adsorption of RuO2 by the functionalized surface of CNF. A better affinity of the oxygen-containing functional groups on CNF toward RuO2 mobilizes relatively faster adsorption of this moiety, leading to a well-controlled segregation of Pt nanoparticles toward the surface. Further reorganization of Pt nanoparticles leads to the formation of a Pt nanosheet structure on the surface. The electrochemical properties of these materials are initially evaluated using cyclic voltammetric analysis. The cyclic voltammetric results indicate that C-PtRuO2 shows a charge storage property, a typical characteristic of hydrous RuO2, whereas F-PtRuO2 shows an oxygen reduction property, which is the characteristic feature of Pt. This clear switch in the behavior from charge storage to electrocatalysis is further confirmed by galvanostatic charge discharge and rotating-disk-electrode studies.